2010
DOI: 10.1016/j.socscimed.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking for cardiac symptoms: Beyond the masculine–feminine binary

Abstract: Empirical and theoretical literature suggests that stereotypical gender roles shape men's and women's health help-seeking behavior, and plays an important role in the treatment seeking delays of cardiac patients. We were interested in exploring the ways in which gender informs the experiences and help-seeking behavior of men and women who experienced the symptoms associated with acute cardiac events. We undertook 20 in-depth interviews between October 2007 and July 2008 with 11 men and 9 women recently diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 47 publications
2
68
0
1
Order By: Relevance
“…Gender comparisons can inadvertently reify dominant ideals of masculinity and femininity in ways that ignore the diversity and efforts of many who take up or purposely employ "other" actions. The work of Galdas, Johnson, Percy, and Ratner (2010) reminds us that gender similarities are important to apprehend-especially as the field seeks to transition descriptive work toward interventions. In summary, the absence of potentially unifying and enriching theoretical frameworks continues to be a significant gap in the research literature.…”
Section: Discussionmentioning
confidence: 99%
“…Gender comparisons can inadvertently reify dominant ideals of masculinity and femininity in ways that ignore the diversity and efforts of many who take up or purposely employ "other" actions. The work of Galdas, Johnson, Percy, and Ratner (2010) reminds us that gender similarities are important to apprehend-especially as the field seeks to transition descriptive work toward interventions. In summary, the absence of potentially unifying and enriching theoretical frameworks continues to be a significant gap in the research literature.…”
Section: Discussionmentioning
confidence: 99%
“…A body of recent work has begun to question the simplistic link between constructions of hegemonic masculinity and men's health-care practices. 239 Evidence of the fluid and contextually dependent nature of gender in the wider body of men's health literature 240,241 suggests that the studies included in our review may not adequately capture the complexity of how masculinities intersect with men's health behaviour. Thus, there is unlikely to be a 'one-size-fits-all' approach to gender-sensitising self-management support for men.…”
mentioning
confidence: 99%
“…While some women also displayed passive and fatalistic values about health, some men contested masculine norms, showing the limits of an essentialist concept of gender. In their study of help seeking for cardiac symptoms, Galdas et al (2010) also demonstrated that while some individuals explicitly positioned their behaviour during the cardiac event as stereotypical of their gender, some behaviours that might be stereotypically considered as masculine or feminine practices were shared by both male and female participants. These results remind us that gender is not always central in the doing of health.…”
Section: Discussionmentioning
confidence: 99%